All-solid-state electrochromic device based on quasi-solid electrolyte and manufacturing method

By using the in situ curing method of quasi -solid electrolyte before the use of quasi -solid electrolyte before the use of quasi -solid electrolyte before, solve the leakage and decomposition of liquid electrolytes, and the high cost and low -electrical rate of all -solid electrolytes. Full -solid -state -to -color discoloration device.

CN119376152APending Publication Date: 2025-01-28NINGBO MI RUO ELECTRONICS TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411196070.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In existing electrochromic devices, liquid electrolytes have problems with liquid leakage and decomposition, while all-solid electrolytes face high costs and low conductivity, making it difficult to meet the demand for rapid discoloration.

Method used

Adopt a full -solid -state electrocarious discoloration device based on quasi -solid electrolyte, set the quasi -solid electrolytic front drive solution by setting up a quasi -solid electrolyte before the first electrical substrate and the second electrical substrate, and to form a high -performance electrical electrophoresis through the integration of the original solidification method. Trimming device.

Benefits of technology

The high -power chemical stability, rapid response characteristics, high -light modulation rate, and long -term cycle stability solve the problems of traditional electrolyte leakage, decomposition and high -cost problems, and meet the application of high -requirements such as modern automotive sunroof and smart windows.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119376152A_ABST
    Figure CN119376152A_ABST
Patent Text Reader

Abstract

The invention discloses an all-solid-state electrochromic device based on a quasi-solid-state electrolyte. The all-solid-state electrochromic device comprises a first conductive substrate, a second conductive substrate and the quasi-solid-state electrolyte clamped between the first conductive substrate and the second conductive substrate. The surface of the first conductive substrate is plated with a tungsten oxide film layer, and the surface of the second conductive substrate is correspondingly plated with another electrochromic material which is in complementary relation with the tungsten oxide electrochromic material; the quasi-solid electrolyte is integrally assembled into the all-solid-state electrochromic device through an in-situ curing method of a quasi-solid electrolyte precursor solution arranged between the first conductive substrate and the second conductive substrate. According to the all-solid-state electrochromic device based on the quasi-solid-state electrolyte, the defects of traditional liquid electrolyte and all-solid-state electrolyte are overcome, and the all-solid-state electrochromic device not only has excellent electrochemical stability and high optical modulation rate, but also shows the quick response characteristic and excellent long-term cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochromism, and in particular to an all-solid-state electrochromism device based on a quasi-solid electrolyte and a manufacturing method thereof. Background Art

[0002] As a smart material technology, electrochromic technology can control the color or transparency of materials through a small external electric field. It is widely used in the fields of automotive sunroofs, smart windows, etc. The performance of electrochromic devices depends largely on the electrolyte materials used. At present, the electrolytes used in electrochromic devices are mainly divided into three types: liquid, quasi-solid and all-solid.

[0003] Although liquid electrolytes have high ionic conductivity, they are prone to leakage and decomposition, which limits the stability and service life of the device. Although all-solid-state electrolytes avoid the problems of leakage and electrolyte decomposition, they usually face challenges such as low conductivity, high preparation cost, and complex process, which limit their commercial application. In addition, the low conductivity of all-solid-state electrolytes will also cause the response time of electrochromic devices to be long, making it difficult to meet the demand for rapid color change.

[0004] As a compromise, quasi-solid electrolytes combine the advantages of liquid and all-solid electrolytes. They are formed by adding polymers or gelling agents to liquid electrolytes, which not only maintains a certain fluidity, but also restricts the free movement of ions to a certain extent. However, the preparation process of traditional quasi-solid electrolytes is complicated, involving multiple steps and condition control, and in practical applications, there are still problems such as poor adhesion between the electrolyte membrane and the electrode interface and easy detachment, which affects the overall performance and reliability of the device. At present, the preparation of quasi-solid electrolytes includes the modification and synthesis of prepolymers, the introduction of conductive ions, and the formation of electrolyte membranes. The modification and synthesis of existing prepolymers require comprehensive consideration of multiple factors, and the process is complex and cumbersome. In addition, pre-forming the electrolyte membrane and then laminating and assembling the electrochromic device may result in poor solid-solid interface, which may cause the electrolyte to detach from the electrode / electrolyte interface, seriously reducing the device performance. For example, in the typical lamination method for assembling electrochromic devices, the high viscosity of the electrolyte membrane may cause defects such as bubbles during lamination, and the poor contact of the lamination process may also lead to a longer device response time, hindering the practical application of electrochromic devices. Summary of the invention

[0005] In view of the above shortcomings of the prior art, the present invention provides an all-solid-state electrochromic device based on a quasi-solid-state electrolyte to solve the problems of leakage and decomposition of liquid electrolytes that are difficult to overcome simultaneously with existing electrolytes, as well as the high cost and low conductivity of all-solid-state electrolytes, and provides an electrochromic device with high electrochemical stability, fast response characteristics, high optical modulation rate and long-term cycle stability to meet the high requirements of modern automobile sunroofs, smart windows and other electrochromic applications.

[0006] In order to achieve the above purpose, the technical solution adopted by the present invention is:

[0007] A fully solid-state electrochromic device based on a quasi-solid-state electrolyte, the fully solid-state electrochromic device comprising a first conductive substrate, a second conductive substrate and a quasi-solid-state electrolyte sandwiched between the first conductive substrate and the second conductive substrate; the surface of the first conductive substrate is coated with a tungsten oxide thin film layer, and the surface of the second conductive substrate is correspondingly coated with another electrochromic material that is complementary to the tungsten oxide electrochromic material; the quasi-solid-state electrolyte is integrated into the fully solid-state electrochromic device by an in-situ solidification method of a quasi-solid-state electrolyte precursor solution disposed between the first conductive substrate and the second conductive substrate.

[0008] As a preferred technical solution, the quasi-solid electrolyte precursor solution is prepared by a one-step solution method.

[0009] As a preferred technical solution, the quasi-solid electrolyte precursor comprises polyethylene oxide, nano inorganic filler, cross-linking agent, colorless photoinitiator and organic solution containing lithium salt. The inventors have found through long-term research and development that polyethylene oxide (PEO) has the advantages of flexibility, low density and good electrode contact characteristics, and has become one of the most promising electrolyte prepolymer candidate materials for electrochromic devices. Its prepolymer solution has high viscosity, which helps to enhance the adhesion strength between the electrolyte layer and the electrode interface. In addition, PEO helps to improve the electrochemical stability of the inorganic electrochromic film during the cyclic voltammetry process, so it has advantages in improving the durability of the electrochromic device (ECD).

[0010] As a preferred technical solution, the mass ratio of polyethylene oxide, nano inorganic filler and cross-linking agent is 0.1-6: 0.003-0.02: 0.4-9; the addition amount of the lithium salt in the quasi-solid electrolyte precursor solution is 0.5-5 mmol / g.

[0011] As a preferred technical solution, the nano inorganic filler includes but is not limited to at least one of nano silicon dioxide, nano aluminum oxide, nano titanium dioxide, nano zirconium oxide, nano magnesium oxide, nano carbon tubes, and nano cerium dioxide.

[0012] As a preferred technical solution, the cross-linking agent includes but is not limited to at least one of polyethylene glycol dimethacrylate, poly(ethylene glycol) methacrylate, and polyethylene glycol diacrylate.

[0013] As a preferred technical solution, the lithium salt includes but is not limited to at least one of LiClO4, LiPF6, LiAsF6, LiBF4, LiAlCl4, LiSCN, LiTaF6, LiSnF6, LiGeF6, LiCF3SO3, LiN(SO2CF3)2, LiTFSI, and LiTf.

[0014] As a preferred technical solution, the organic solution includes but is not limited to at least one high boiling point organic solution selected from the group consisting of propylene carbonate, ethylene carbonate, diethyl carbonate, vinylene carbonate, dimethyl carbonate, N-methylpyrrolidone, butyl acetate, dimethyl sulfoxide, N,N-dimethylformamide, dimethylacetamide, γ-butyrolactone, and tetrahydrofuran.

[0015] As a preferred technical solution, the in-situ curing method uses ultraviolet irradiation to cure the quasi-solid electrolyte precursor solution, so that the first conductive substrate, the quasi-solid electrolyte and the second conductive substrate are assembled into one.

[0016] Another aspect of the present invention is to provide a method for manufacturing the all-solid-state electrochromic device based on the quasi-solid electrolyte as described above, the manufacturing method comprising the following steps:

[0017] S1: Weigh a certain amount of polyethylene oxide and nano inorganic filler particles by weight and place them in a brown reagent bottle, then add a certain amount of cross-linking agent and colorless photoinitiator to the reagent bottle, and then add an organic solution of a certain concentration of lithium salt to the reagent bottle, and stir the mixed solution for a certain period of time in a light-proof and warm water bath to obtain a quasi-solid electrolyte precursor solution;

[0018] S2: Place height-limited particles of a certain size around the second conductive substrate coated with another electrochromic material that is complementary to the tungsten oxide electrochromic material, transfer a certain amount of the quasi-solid electrolyte precursor solution obtained in step S1, and drip it on the electrochromic thin film layer of the second conductive substrate; then cover the first conductive substrate coated with the tungsten oxide thin film layer on the second conductive substrate, apply a certain pressure, place it under an ultraviolet lamp for a certain period of time for in-situ curing and assembling into the integrated all-solid-state electrochromic device.

[0019] The present invention successfully solves the limitations of traditional liquid and all-solid electrolytes in the application of electrochromic devices, such as the leakage and decomposition problems of liquid electrolytes, and the high cost and low conductivity problems of all-solid electrolytes. By introducing polyethylene oxide (PEO) as an additive for quasi-solid electrolytes, the present invention not only simplifies the preparation process and avoids the complicated polymer synthesis and modification steps, but also effectively improves the ionic conductivity of the electrolyte and the adhesion strength with the electrode.

[0020] In addition, the in-situ curing integrated assembly technology adopted by the present invention improves the interface contact between the electrolyte and the electrode, solves the problem of easy detachment of the solid-solid interface, and thus significantly improves the cycle life of the electrochromic device. The addition of PEO also enhances the electrochemical stability and helps to improve the durability of the device. In terms of optical performance, the electrochromic device of the present invention exhibits a fast response time and a high optical modulation rate. After long-term cyclic use, it can still maintain excellent cycle stability and optical modulation performance. These characteristics make the present invention have significant technical advantages and application potential in the field of electrochromic devices.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The all-solid-state electrochromic device based on the quasi-solid electrolyte of the present invention uses a one-step solution method to compound a quasi-solid electrolyte precursor solution, combined with an in-situ curing method integrated assembly process, not only provides an electrochromic device with a simple structure and superior performance, but also achieves a significant improvement in device performance by optimizing the composition and preparation process of the quasi-solid electrolyte; on the one hand, it solves the leakage and decomposition problems of traditional electrolytes in electrochromic devices, while avoiding the high cost and low conductivity problems of all-solid-state electrolytes; on the other hand, it effectively improves the ionic conductivity of the electrolyte and the adhesion strength with the electrode, significantly improving the cycle life of the electrochromic device. In addition, the all-solid-state electrochromic device of the present invention has high electrochemical stability, fast response characteristics and high optical modulation rate, meeting the high requirements of modern automobile sunroofs, smart windows and other electrochromic applications.

[0023] In general, the all-solid-state electrochromic device of the present invention overcomes the limitations of the prior art through innovative material selection and manufacturing processes, and provides a more reliable and cost-effective solution. These technical improvements not only enhance the practicality and economy of electrochromic devices, but also broaden their application scope in the field of intelligent control, and have important commercial value and market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a schematic diagram of assembling an electrochromic device using the quasi-solid electrolyte precursor solution and the in-situ curing method of the present invention.

[0025] Figure 2 a to 2f are test graphs of electrochemical and optical properties of the all-solid-state electrochromic device of Example 1 of the present invention.

[0026] Figure 3 a and 3b are scanning electron microscope images of the surface morphology of the quasi-solid electrolyte membrane of comparative example 1 without PEO and example 1 with PEO of the present invention.

[0027] Figure 4 a, 4b and 4c are stress-strain curves, Nyquist plots and transmission spectra obtained by testing quasi-solid electrolytes with different polyethylene oxide (PEO) concentrations in Examples 1 to 6 of the present invention and Comparative Example 1, respectively. DETAILED DESCRIPTION

[0028] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.

[0029] Example 1

[0030] The present embodiment is a method for manufacturing an all-solid-state electrochromic device based on a quasi-solid electrolyte, such as Figure 1 As shown, it includes the following steps:

[0031] S1: Weigh 10.64g (0.1mol) of LiClO4 powder with an analytical balance and place it in a beaker, then use a measuring cylinder to measure 100ml of propylene carbonate (PC) and add it to the beaker to dissolve the LiClO4 powder to obtain a 1mol / L LiClO4-PC liquid electrolyte. Subsequently, weigh 1.8g of polyethylene oxide (PEO) and 0.015g of nano-silicon dioxide (SiO2) particles with an analytical balance and place them in a brown reagent bottle, then add 2.7g of polyethylene glycol diacrylate (PEGDA) as a crosslinker and 0.075g of 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP) as a colorless photoinitiator to the reagent bottle. After that, add 10.5g of 1mol / L LiClO4-PC solution to the reagent bottle, and stir the above mixed solution for 8h in a light-proof and water bath at 30°C to obtain a quasi-solid electrolyte precursor solution.

[0032] S2: Place spacers with a diameter of 150 μm around ITO glass (abbreviated as NiO / ITO / glass, the ITO glass serves as the second conductive substrate) coated with a nickel oxide thin film layer, use a dropper to transfer a certain amount of quasi-solid electrolyte precursor solution (electrolyte), drop a few drops of the quasi-solid electrolyte precursor solution on the nickel oxide (NiO) film, and then cover the ITO glass (abbreviated as glass / ITO / WO3, the ITO glass serves as the first conductive substrate) coated with a tungsten oxide thin film layer on the NiO / ITO / glass. After applying a certain pressure, place it under a UV lamp for 2 minutes for in-situ curing and assembly into an integrated all-solid-state electrochromic device (abbreviated as: glass / ITO / WO3 / QSPE / NiO / ITO / glass, where QSPE represents the quasi-solid electrolyte of the present application).

[0033] The electrochemical and optical performance tests of the all-solid-state electrochromic device of this embodiment are as follows. Figure 2 a to 2f, where Figure 2 a represents the cyclic voltammetry (CV) curve at a scan rate of 100 mV / s; Figure 2 b represents the switching time and transmittance variation curves at wavelength λ = 633nm and voltage ±1.4V; Figure 2 c represents the changes of optical density (ΔOD) and charge density (Q) at a wavelength of 633 nm; Figure 2 d indicates WO3-NiO complementary ECD at 0.28 mA / cm 2 Charge and discharge cycle performance under current density; Figure 2 e shows the transmission spectra of ECD in the bleached and colored states at a voltage of ±1.4 V (initial and after 15000 cycles); Figure 2 f represents the in-situ transmission spectrum of the ECD before and after 20,000 long cycles (±1.4 V, 20 seconds per cycle). Specifically, Figure 2 a In the potential range of -1.4V to +1.4V, 300 CV cycles were performed at a scan rate of 100mV / s, and the CV curves had high repeatability, which indicated that the working characteristics of the ECD did not change significantly and that the ECD had excellent electrochemical stability. Figure 2 As shown in b, a potential of ±1.4 V was applied to obtain the in-situ transmittance of ECD at a wavelength of λ = 633 nm. It can be found that the response times of ECD bleaching (0.96 s) and coloration (3.48 s) are very short. Figure 2 The calculated coloring efficiency (CE) of ECD is 93.93 cm 2 / C, which may be because PEO reduces ion diffusion and thus increases the CE value. This result also emphasizes the better electron utilization efficiency of ECD. Figure 2 As shown in d, using 0.28 mA / cm 2 The long-term capacitance retention of the ECD was evaluated by measuring the current density of the electrode. After 7,000 cycles, the capacitance retention reached 90%; after 15,000 cycles, the capacitance retention was 77.9%. Figure 2 e shows the in-situ optical spectra of the ECD during the initial stage of cycling and after cycling for more than 15,000 times. The maximum optical modulation rate of the ECD reaches 36.19% (633 nm), which is 30.92% higher than the initial value. Figure 2 f shows that the in-situ optical modulation of the device at a wavelength of 633 nm does not decay after 20,000 switching cycles, indicating that the quasi-solid electrolyte contributes to the excellent cyclic stability of the ECD.

[0034] Comparative Example 1

[0035] The manufacturing method of the all-solid-state electrochromic device based on the quasi-solid electrolyte in this comparative example is basically the same as that in Example 1, except that polyethylene oxide (PEO) is not added in the manufacturing method of this comparative example, and its performance curve corresponds to Figure 4 The P0 curve in .

[0036] In addition, the surface morphology of the electrolyte membranes prepared in Example 1 and Comparative Example 1 was analyzed by scanning electron microscopy. Figure 3 Specifically, Figure 3 3a and 3b are SEM images of the electrolyte membranes of Comparative Example 1 without PEO and Example 1 with PEO, respectively. The electrolyte membrane of Comparative Example 1 without PEO has a smooth surface, and the electrolyte membrane of Example 1 with PEO exhibits porous structure characteristics. The increase in the number of porous structures of the quasi-solid electrolyte is due to the addition of high-crystallinity PEO. Smoothness indicates that it is not conducive to forming a good contact interface with the electrode film, while the porous structure can increase the specific surface area, improve the interface contact and ion conductivity, which indicates that the quasi-solid electrolyte with PEO added in this application has better performance.

[0037] Examples 2 to 6

[0038] The raw materials and the manufacturing methods of the all-solid-state electrochromic devices based on the quasi-solid electrolyte of Examples 2 to 6 are basically the same as those of Example 1, except that the added masses of polyethylene oxide (PEO) in Examples 2 to 6 are 0.45 g, 0.9 g, 1.35 g, 2.25 g, and 2.7 g, respectively, corresponding to Figure 4 The P10, P20, P30, P50, and P60 curves in Example 1 correspond to Figure 4 The P40 curve in .

[0039] The quasi-solid electrolytes with different polyethylene oxide (PEO) concentrations prepared in Examples 1 to 6 and Comparative Example 1 were subjected to performance tests. The results are as follows: Figure 4 a to Figure 4 c. Specifically, Figure 4 a represents the stress-strain curve of PEO electrolytes with different concentrations, indicating that the addition of PEO can improve the shear strength of the quasi-solid electrolyte. When the quasi-solid electrolyte and the electrode form an electrochromic device, it can act as a binder to promote good adhesion between the electrolyte and the electrochromic layer, thereby improving the device performance. Figure 4 b It is found that as the PEO concentration increases, the bulk resistance R b The electrolyte is made into a sandwich structure (glass / ITO / WO3 / QSPE / NiO / ITO / glass), and its optical transparency in the wavelength range of 320 to 1000nm is measured. The transmittance curve is as follows Figure 4 c. All electrolyte samples exhibit excellent optical transparency (>85%@633nm), and the transmittance in the visible and infrared spectra is close to or even exceeds that of glass.

[0040] It can be seen that the patent of the present invention has considerable advantages over the currently used technology. The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may have various changes and improvements without departing from the spirit and scope of the present invention, and these changes and improvements fall within the scope of the present invention to be protected.

Claims

1. An all-solid-state electrochromic device based on a quasi-solid electrolyte, characterized in that: The all-solid-state electrochromic device comprises a first conductive substrate, a second conductive substrate and a quasi-solid electrolyte sandwiched between the first conductive substrate and the second conductive substrate; the surface of the first conductive substrate is coated with a tungsten oxide thin film layer, and the surface of the second conductive substrate is correspondingly coated with another electrochromic material that is complementary to the tungsten oxide electrochromic material; the quasi-solid electrolyte is integrated into the all-solid-state electrochromic device by an in-situ solidification method of a quasi-solid electrolyte precursor solution arranged between the first conductive substrate and the second conductive substrate.

2. The all-solid-state electrochromic device based on a quasi-solid electrolyte according to claim 1, characterized in that: The quasi-solid electrolyte precursor solution is prepared by a one-step solution method.

3. The all-solid-state electrochromic device based on a quasi-solid electrolyte according to claim 1, characterized in that: The quasi-solid electrolyte precursor comprises polyethylene oxide, nano inorganic filler, a cross-linking agent, a colorless photoinitiator and an organic solution containing lithium salt.

4. The all-solid-state electrochromic device based on a quasi-solid electrolyte as claimed in claim 3, characterized in that: The mass ratio of the polyethylene oxide, the nano inorganic filler and the cross-linking agent is 0.1-6: 0.003-0.02: 0.4-9; the addition amount of the lithium salt in the quasi-solid electrolyte precursor solution is 0.5-5 mmol / g.

5. The all-solid-state electrochromic device based on a quasi-solid electrolyte as claimed in claim 3, characterized in that: The nano inorganic filler includes but is not limited to at least one of nano silicon dioxide, nano aluminum oxide, nano titanium dioxide, nano zirconium oxide, nano magnesium oxide, nano carbon tubes, and nano cerium dioxide.

6. The all-solid-state electrochromic device based on a quasi-solid electrolyte as claimed in claim 3, characterized in that: The cross-linking agent includes but is not limited to at least one of polyethylene glycol dimethacrylate, poly(ethylene glycol) methacrylate, and polyethylene glycol diacrylate.

7. The all-solid-state electrochromic device based on a quasi-solid electrolyte as claimed in claim 3, characterized in that: The lithium salt includes but is not limited to at least one of LiClO4, LiPF6, LiAsF6, LiBF4, LiAlCl4, LiSCN, LiTaF6, LiSnF6, LiGeF6, LiCF3SO3, LiN(SO2CF3)2, LiTFSI, and LiTf.

8. The all-solid-state electrochromic device based on a quasi-solid electrolyte as claimed in claim 3, characterized in that: The organic solution includes, but is not limited to, at least one high boiling point organic solution selected from the group consisting of propylene carbonate, ethylene carbonate, diethyl carbonate, vinylene carbonate, dimethyl carbonate, N-methylpyrrolidone, butyl acetate, dimethyl sulfoxide, N,N-dimethylformamide, dimethylacetamide, γ-butyrolactone, and tetrahydrofuran.

9. The all-solid-state electrochromic device based on a quasi-solid electrolyte according to claim 1, characterized in that: The in-situ curing method uses ultraviolet irradiation to cure the quasi-solid electrolyte precursor solution, so that the first conductive substrate, the quasi-solid electrolyte and the second conductive substrate are assembled into one.

10. A method for manufacturing an all-solid-state electrochromic device based on a quasi-solid electrolyte according to any one of claims 1 to 9, characterized in that: The production method comprises the following steps: S1: Weigh a certain amount of polyethylene oxide and nano inorganic filler particles by weight and place them in a brown reagent bottle, then add a certain amount of cross-linking agent and colorless photoinitiator to the reagent bottle, and then add an organic solution of a certain concentration of lithium salt to the reagent bottle, and stir the mixed solution for a certain period of time in a light-proof and warm water bath to obtain a quasi-solid electrolyte precursor solution; S2: Place height-limited particles of a certain size around the second conductive substrate coated with another electrochromic material that is complementary to the tungsten oxide electrochromic material, transfer a certain amount of the quasi-solid electrolyte precursor solution obtained in step S1, and drip it on the electrochromic thin film layer of the second conductive substrate; then cover the first conductive substrate coated with the tungsten oxide thin film layer on the second conductive substrate, apply a certain pressure, place it under an ultraviolet lamp for a certain period of time for in-situ curing and assembling into the integrated all-solid-state electrochromic device.

Citation Information

Cited By

  • Solid electrolyte, preparation method thereof and electrochromic device

    CN120686504A